Efficiency performance of paddy farming in east and west coast of Peninsular Malaysia - Lim, Ghee Thean; Ismail, Mohd Mansor (Academic Journals, 2013)
Paddy farming activity is in full swing in both east and west coast of Peninsular Malaysia, this was due to rice is a staple food for Malaysian and national food security. This study examined technical efficiency of paddy farming in east and west coast of Peninsular Malaysia by using data envelopment analysis. Besides, this study also attempted to investigate determinants of inefficiency by using Tobit regression. Information was collected through direct survey interview on a sample of 230 paddy farmers from Peninsular Malaysia. Average efficiency scores of paddy farming for the whole of Peninsular Malaysia, east and west coast had been estimated at 55.6, 51.7 and 63.1%, respectively. The variable tractor had been found positively and significantly affected inefficiency in the east coast of Peninsular Malaysia. On the other hand, inefficiency was found significantly and negatively affected by the variable seminar in the west coast. Efficiency performance of west coast in paddy farming was considered better off than the east coast. In brief, both east coast and west coast of Peninsular Malaysia had indicated relatively low efficiency performance. Encouragement of attending seminar in west coast of Peninsular Malaysia for regularly updating new technology and information should be done by authorities in order to improve efficiency performance of paddy farming.